Pengaruh Struktur Modal Dan Profitabilitas Terhadap Terhadap Nilai Perusahaan Studi Kasus Pada Pt. Astra Internasional Tbk Tahun 2021-2025 - Jason Angsana; Romli Romli; Istiono Istiono (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the effect of capital structure and profitability on firm value at PT Astra International Tbk during the 2021–2025 period. Capital structure was proxied by Debt to Equity Ratio (DER), profitability by Return on Assets (ROA), and firm value by Price to Book Value (PBV). This research employed a quantitative approach using secondary data obtained from the company’s quarterly financial statements through the Stockbit platform. The data were analyzed using multiple linear regression with the assistance of SPSS version 23 software. The results indicate that partially, capital structure has a negative and significant effect on firm value, as indicated by a significance value of 0.006 < 0.05. Meanwhile, profitability has a negative but insignificant effect on firm value, with a significance value of 0.858 > 0.05. Simultaneously, capital structure and profitability significantly affect firm value, with a significance value of 0.019 < 0.05. The coefficient of determination of 37.4% shows that DER and ROA are able to explain variations in firm value, while the remaining percentage is influenced by other variables outside this study.